Risk Management for 4-H Youth Development Work: Records - Paula M. Davis; Dale Pracht; Stefanie Prevatt; Janet Psikogios; Marilyn Norman; Kate Forgarty; Jean Hink (EDIS)
This 2-page publication is one in the series Risk Management for 4-H Youth Development Work. It discusses the use of records among 4-H participants. Written by Paula Davis, Dale Pracht, Stefanie Prevatt, Janet Psikogios, Marilyn Norman, Kate Fogarty, and Jean Hink and published by the UF/IFAS 4-H Youth Development Department, February 2018. http://edis.ifas.ufl.edu/4h387